Comparison of laboratory performance of asphalt mixes containing different proportions of RAS and RAP. (15th October 2016) - Ghabchi, Rouzbeh; Barman, Manik; Singh, Dharamveer; Zaman, Musharraf; Mubaraki, Muhammad Ali
Highlights: Screening the mixes for fatigue life is missing in current mix design procedures. Incorporation of more than 6% RAS, significantly reduced the fatigue life of HMA. Using RAP and RAS in HMA reduced its resistance to low-temperature cracking. Abstract: Despite environmental and economic advantages associated with incorporating recycled asphalt shingles (RAS) and reclaimed asphalt pavement (RAP) in hot-mix asphalt (HMA), concerns focus on fatigue and low-temperature cracking potential of pavements containing RAS and RAP. This study was undertaken to identify the areas in need for research through conducting a national survey among departments of transportation and to evaluate the effects of RAS and RAP on fatigue, low-temperature cracking and stiffness of HMA. National survey results indicated that while the fatigue cracking is the major concern when RAS and/or RAP are used in mixes, no specific test is recommended for fatigue evaluation of these mixes at the mix design stage. It was found that, fatigue life of mixes with a non-polymer-modified binder containing a blend of 5% RAS and 5% RAP led to the maximum increase in fatigue life. However, incorporation of 6% RAS decreased the fatigue life of mixes, when compared with virgin mix. Also, it was found that addition of RAS and/or RAP to asphalt mixes increased their dynamic moduli which may result in a better rutting performance. From creep compliance test results it was concluded that use of RAS and/or RAP may lead to a higher low-temperature cracking potential when compared with the virgin mixes. Findings of this study can be used to develop/update guidelines/special provisions for design of HMA containing RAS and RAP.